The genetic basis of epidermolysis bullosa simplex with mottled pigmentation. - Uttam, Jai; Hutton, E.; Coulombe, P. A.; Anton-Lamprecht, Ingrun; Yu, Q. C.; Gedde-Dahl, T.; Fine, J. D.; Fuchs, E. (Proceedings of the National Academy of Sciences of the United States of America, 1996)
Epidermolysis bullosa simplex (EBS) is a group of autosomal dominant skin diseases - characterized by blistering, due to mechanical stress-induced de...
Gesehen am 27.09.2023